Validação do diagnóstico de enfermagem fadiga em pacientes com doença renal crônica - Menezes, Angélica Paixão de (2019)
The aim of this study is to verify the validity of the nursing diagnosis Fatigue in patients with Chronic Kidney Disease based on two steps: content analysis and clinical validation. In the first stage, 31 specialist nurses in nursing diagnosis and/or nephrology participated, from January to March 2018, through a questionnaire. The etiological factors considered relevant to the nursing diagnosis Fatigue (CVI ≥ 0.80): Increased urea level; Anemia; Protein-calorie malnutrition; Sleep disorders; Neuromuscular disorders; Increased Pro- inflammatory Cytokines; Low sodium content in the dialysate; Depressed mood; Anxiety; Age. The following clinical indicators obtained CVI ≥ 0.80: Lethargy; Somnolence; Disinterest in the environment that surrounds him; Decreased attention span; Decreased patience; Change in concentration; Increased need for rest and malaise. Related to the clarity and precision of the definitions of the etiological factors, they presented CVIs ≤ 0.80: Anemia (clarity of the operational); Protein-caloric malnutrition (clarity and precision of the operational). All clinical indicators were considered clear and accurate. Clinical validation took place from September 2018 to January 2019, with 120 patients with Chronic Kidney Disease on hemodialysis, monitored in two reference services. The collection involved physical assessment and consultation of the medical record. For the analysis, the Latent Class method, the Chi-square test, Fisher's exact probability test, Odds Ratio, Kolmogorov-Smirnov tests, Levene's test, t test or Mann-Whitney test and a model of logistic regression. All recommendations of resolution no 466/2012 were complied with. The estimated prevalence of the nursing diagnosis Fatigue was 80.54%. The most frequent clinical indicators: Increased need for rest (74.2%); Drowsiness (71.7%); Alteration in Libido (59.2%); Introspection (55.0%); and Fatigue (54.2%). Indicators with high specificity values: Increased need for rest (0.9964); Decreased patience (0.9988); Lethargy (0.9999); and Impaired ability to maintain the usual level of physical activity (0.9999). The most frequent etiological factors: Increased urea level (95.8%); Anemia (71.7%); Increase in physical effort (54.2%); and Environmental 11 barriers (53.3%). The presence of Anxiety, Non-stimulating lifestyle, Depressed mood and stressors factors increased the chance of developing Fatigue by 2.6 times (p=0.033), 3.2 times (p=0.017), 2.3 times (0.045) and 2.5 times (0.035), respectively. Hemoglobin was significantly lower in the presence of the ND Fatigue (p= 0.040). On the other hand, the scores on the Sleep Disturbance (p= 0.030) and Anxiety (p=0.007) scales were statistically higher in the presence of the ND Fatigue. Patients with the factors Increased urea level; Anemia; Sleep disorders; Interdialytic weight gain; Low sodium content in the dialysis solution; Depressed mood; Anxiety; Non-stimulating lifestyle; Lack of physical conditioning; Increased physical exertion; Stressors; Environmental barriers; Negative life event; and Job Demands, had an increased chance of developing Fatigue of 1.008; 1.092; 1.114; 2.294; 7.333; 1.101; 1.109; 6.667; 3.273; 4.417; 5.222; 3.923; 3,666 and 2,833 times, respectively. The validation of the nursing diagnosis Fatigue allowed the evaluation of its elements in the context of Chronic Kidney Disease, of the respective definitions, as well as reflections on the NANDA-I taxonomy in the studied context.